ANALISIS SISTEM PENGENDALIAN INTERNAL TERHADAP PEMUTUSAN KREDIT USAHA MIKRO, KECIL DAN MENENGAH (Studi Kasus pada Bank Sinarmas dan BRI Cabang Palangkaraya) - Meirilin Esterina; Unti Ludigdo (Jurnal Ilmiah Mahasiswa FEB, 2015)
This research has a purpose to know the internal control system of the credit decision micro, small and medium Sinarmas Bank and Bank Rakyat Indonesia (BRI) Branch Palangkaraya. The research used qualitative descriptive method. Thus, the research is about explaining a certain situation and condition, analyze and compare between Bank Sinarmas and BRI Branch Palangkaraya. In fact, there were some differences between the branch of Sinarmas Bank and the branch of BRI bank in Palangkaraya. The differences were : lending banks, collateral appraisal, disbursement decisions, type of loans, and the bank group. In sinarmas bank branch Palangkaraya, the collateral appraisal was implemented by the back office employess. However, BRI bank branch palangkaraya had their own particular employees in implementing the collateral appraisal. The suggestion that can be given to the Sinarmas Bank is to put on additional division that can handle the collateral appraisal specifically. It is expexted to help the process of lending and increase the performance of the third party funds. Then, BRI Bank should add a legal section to check the validity of credit documents in order to facilitate the loan process at the branch of BRI Bank in Palangkaraya. By the advice given, it is expected to help the process of granting credit and prevent the possibility of acts of fraud that can occur in both banks.   Keywords: Business Credit, SMEs, Internal Control